2021
DOI: 10.4103/aca.aca_46_19
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting right ventricular systolic dysfunction in high-risk patients undergoing non-emergent open abdominal surgery

Abstract: Background: The prognostic value of right ventricular systolic dysfunction in high-risk patients undergoing non-emergent open abdominal surgery is unknown. Here, we aim to evaluate whether presence of preexisting right ventricular systolic dysfunction in this surgical cohort is independently associated with higher incidence of postoperative major adverse cardiac events and all-cause in-hospital mortality. Methods: This is a single-centered retrospective study. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Due to the small number of dialysis outcomes, we were unable to adjust to any other differences in RV function groups. Still, this finding is pathophysiologically plausible as RV failure can cause a reduction in cardiac output resulting in decreased renal blood flow [ 24 ] and increased venous congestion [ 25 ] but is inconsistent with a prior small cohort study demonstrating an association between RV dysfunction and mortality, but not with dialysis [ 26 ]. However, even though RV dysfunction has been prospectively predictive of mortality in patients with chronic kidney disease [ 27 ], research into the relationship between pulmonary hypertension, RV dysfunction and chronic kidney disease is in its infancy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the small number of dialysis outcomes, we were unable to adjust to any other differences in RV function groups. Still, this finding is pathophysiologically plausible as RV failure can cause a reduction in cardiac output resulting in decreased renal blood flow [ 24 ] and increased venous congestion [ 25 ] but is inconsistent with a prior small cohort study demonstrating an association between RV dysfunction and mortality, but not with dialysis [ 26 ]. However, even though RV dysfunction has been prospectively predictive of mortality in patients with chronic kidney disease [ 27 ], research into the relationship between pulmonary hypertension, RV dysfunction and chronic kidney disease is in its infancy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Outside of the cardiac surgical setting, the prevalence of pre-existing RVD in surgical populations has seen limited study; however, what data does exist (Table 1) suggests a prevalence of anywhere between 5.7 and 100% and a profound effect on clinical outcomes. Prevalence figures naturally vary depending on patient population and definition of RVD -in the majority of studies, RVD is defined as 'normal' versus 'abnormal' on the basis of visual inspection on echocardiography images resulting in a relatively consistent estimate of the prevalence in the region of 5.7-11% (Chou et al 2021;Chou et al 2019;Joseph et al 2021;Meyer et al 2023). Reflecting an extreme estimate of incidence, Kim et al however examined RV function in 78 patients with mean age of 80.1 (9.1) years who had sustained a fractured hip and observed that RVD as defined by abnormal RV global longitudinal strain on 2D-speckle tracking was present in all (100%) patients (Kim et al 2017).…”
Section: Pre-existing Rvdmentioning
confidence: 99%
“…Reflecting an extreme estimate of incidence, Kim et al however examined RV function in 78 patients with mean age of 80.1 (9.1) years who had sustained a fractured hip and observed that RVD as defined by abnormal RV global longitudinal strain on 2D-speckle tracking was present in all (100%) patients (Kim et al 2017). Both pre-existing RVD and RV dilatation have been associated with increased incidence of complications and/or mortality in patients undergoing vascular, abdominal, orthopaedic, and renal transplant surgery (Chou et al 2021;Chou et al 2019;Joseph et al 2021;Kim et al 2017) (Table 1).…”
Section: Pre-existing Rvdmentioning
confidence: 99%